Acute cytomegalovirus hepatitis in immunocompetent host - Al-Mahtab, Mamun; Rahman, S; Khan, M (Kathmandu University Medical Journal, 2009)
Background: In inmunocompetent hosts, cytomegalovirus (CMV) infection is generally asymptomatic. It may however present as infectious mononucleosis. Serious complications have rarely been reported. We report three cases of acute CMV hepatitis in immunocompetent men for the first time from Bangladesh. All three presented to us with features of acute hepatitis of variable duration preceded by prodrome. Other probable causes of acute hepatitis were ruled out and none had any clinical stigmata of cirrhosis. All the three patients underwent uneventful recovery. Although more common in the immunocompromised, CMV can occasionally produce symptomatic hepatitis in the immunocompetent host. Disease is self limiting, but supportive measures are needed. Key words: Cytomegalo virus, Acute hepatitis, Immunocompetent host doi: 10.3126/kumj.v7i1.1772 Kathmandu University Medical Journal (2009), Vol. 7, No. 1, Issue 25, 79-81